Dopaminergic modulation of novelty repetition in Parkinson's disease: A study of P3 event-related brain potentials. Issue 12 (December 2020) - Bertram, Malte; Warren, Claire V.; Lange, Florian; Seer, Caroline; Steinke, Alexander; Wegner, Florian; Schrader, Christoph; Dressler, Dirk; Dengler, Reinhard; Kopp, Bruno
Highlights: All participants showed robust novelty P3 waveforms during both testing sessions. Patients who were tested on medication during a first session, showed enhanced novelty P3 amplitudes during a second session (off medication). Our results demonstrate the necessity for properly controlled repeated-measures designs to isolate diagnosis or medication effects and novelty or repetition effects. Abstract: Objective: Parkinson's Disease (PD) is a neurodegenerative disease caused by the loss of dopaminergic neurons. Cognitive impairments have been reported using the event-related potential (ERP) technique. Patients show reduced novelty P3 (nP3) amplitudes in oddball experiments, a response to infrequent, surprising stimuli, linked to the orienting response of the brain. The nP3 is thought to depend on dopaminergic neuronal pathways though the effect of dopaminergic medication in PD has not yet been investigated. Methods: Twenty-two patients with PD were examined "on" and "off" their regular dopaminergic medication in a novelty 3-stimulus-oddball task. Thirty-four healthy controls were also examined over two sessions, but received no medication. P3 amplitudes were compared throughout experimental conditions. Results: All participants showed sizeable novelty difference ERP effects, i.e. nd P3 amplitudes, during both testing sessions. An interaction of diagnosis, medication and testing order was also found, indicating that dopaminergic medication modulated nd P3 in patients with PD across the two testing sessions: We observed enhanced nd P3 amplitudes from PD patients who were off medication on the second testing session. Conclusion: Patients with PD 'off' medication showed ERP evidence for repetition-related enhancement of novelty responses. Dopamine depletion in neuronal pathways that are affected by mid-stage PD possibly accounts for this modulation of novelty processing. Significance: The data in this study potentially suggest that repetition effects on novelty processing in patients with PD are enhanced by dopaminergic depletion.